Estrabismo convergente y ambliopía en ojo derecho en paciente masculino de 4 años Presentación de caso. - Cabello Gavilanes, Jackson Joel (2021)
Among children, one of the main affections to their visual health is strabismus, which is a disorder where the eyes do not go in the same direction, generating aesthetic consequences and discomfort in binocular vision. Among the causes that cause it can be mentioned injuries to the optic nerve and the malfunction of the muscles that have the function of controlling the eyes. Its detection and proper treatment is vitally important. When it is not treated in time, it is a cause of amblyopia. The present case study deals with a 4-year-old male patient who presents convergent strabismus and has developed amblyopia in the right eye, which hinders his daily activities. Examinations such as sensory study, determination of visual acuity were performed. Ocular dominance, prism measurement by White's method. The patient shows accommodative bilateral esotropia, he is referred to an ophthalmologist for a retinoscopy under cycloplegia. Correction is applied with bifocal prismatic lenses which have achieved a rehabilitation of 80%.